St. Joseph Abbey 75376 River Road St. Benedict, LA 70457 A Letter Concerning the Spiritual Life - Huerre, Denis (Cistercian studies quarterly, 2016)
SOME YOUNG PROFESSED, monks and nuns, say they seek a few words from an elder. The following is intended as a letter addressed by this elder, "to you who seek to open your heart that you might grow in the spiritual life".